PENINGKATAN KEMAMPUAN MENULIS EKSPOSISI MENGGUNAKAN STRATEGI PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION - Farel Olva Zuve (STKIP ROKANIA, 2016)
This action research generally purpose to improve the skills of writing of exposition in 7th Grade SMPN 18 Padang by cooperative learning strategy of group investigation. The instrument of test and the quotionaire analyzed by quantitative approach and the teachers and students observation analyzed by qualitative approach, reciprocally by field notes. The results of the research was indicated the enhancement of the skills of writing exposition in 7th Grade SMPN 18 Padang used by the cooperatif learning strategy of group investigation. Approximately the score of students writing was 82.66, by indicator of: main idea; 78.9, idea organize; 93,45, discourse; 75.15, style of language; 82.87, and writing mechanism; 81.11. based on the research, it can be concluded that the skills of writing exposition by cooperative learning strategy in 7th in SMPN 18 Padang could improved the writing exposition skill of 7th Grade in SMPN 18 Padang